Les élections européennes en Bulgarie de 2104: élections en crises - Gueorguieva, Petia (2014)
Abstract: The article aims to analyze the European elections held in Bulgaria on 25 of May 2014, the parties and their appeals and performances. The country is among the latest comers in the UE with severe failures in the implementation of the required reforms in the fields of the Rule of Law, fighting corruption and organized crime and reforming the judiciary. The analysis underlines the "second order" character of the 2014 European elections in Bulgaria, held in the context of multiples crisis of different levels. Voters sanctioned severely the parties in government and opened the way to early parliamentary elections